Animation, New Habit Solution In Creative TV Ads Content to Survive from Endemic Covid-19 - Ehwan Kurniawan (Journal of Art, Film, Television, Animation, Games and Technology, 2022)
Corona virus disease 2019, (COVID-19) around the world. The disease is caused by a new type of coronavirus. Until now this causes all creative people have difficulty in activities outside the home.  So there is a change in working communication through virtual to interact with friends, family, and working from client to producer or creator. That situation making creative people to adaptive for new normal habit to innovating content in televison advertising work still can be exciting. They work on an ad campaign for a cutting-edge product or social campaign that will change the world or revolutionize how people live their lives. The method used in this research is through various stages and strategies as follows: research strategy, this research is descriptive-qualitative in nature whose attention is focused on the form of search by means of library observations and the process of direct observation on television and media websites and youtube channels. A lot of content in TV Ads using a solution with animation that seems to move, because of the brain's ability to always save or remember images that were seen before. This can be an obstacle, but also an opportunity in the midst of this crisis. For animation studios this might be a great opportunity, because the animation coordinating work can be done remotely, it has become part of the ecosystem in the animation industry, so that pandemic condition does not become an obstacle for actors in animation studios, so it can be seen during the pandemic. in many ad impressions using a creative approach using animation.